2010
DOI: 10.1371/journal.pone.0013577
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Expression Patterns of Inflammatory and Immune Response Genes Associated with Obesity and NASH in Morbidly Obese Patients

Abstract: BackgroundObesity modulates inflammation and activation of immune pathways which can lead to liver complications. We aimed at identifying expression patterns of inflammatory and immune response genes specifically associated with obesity and NASH in the liver of morbidly obese patients.Methodology/Principal FindingsExpression of 222 genes was evaluated by quantitative RT-PCR in the liver of morbidly obese patients with histologically normal liver (n = 6), or with severe steatosis without (n = 6) or with NASH (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
181
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 210 publications
(200 citation statements)
references
References 56 publications
(59 reference statements)
16
181
1
2
Order By: Relevance
“…Recent evidence involving morbidly obese patients with NASH etiology has been strongly associated with a specific increase in the liver expression of a wide array of proinflammatory M1 cytokines, especially IL-1b (Bertola et al, 2010). Recent reports from our laboratory have shown that CYP2E1-induced oxidative stress causes up-regulation of pattern recognition receptor P2X7r (purinergic receptor X7), which has a direct role in activation of T H 1 cells (Das et al, 2013b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence involving morbidly obese patients with NASH etiology has been strongly associated with a specific increase in the liver expression of a wide array of proinflammatory M1 cytokines, especially IL-1b (Bertola et al, 2010). Recent reports from our laboratory have shown that CYP2E1-induced oxidative stress causes up-regulation of pattern recognition receptor P2X7r (purinergic receptor X7), which has a direct role in activation of T H 1 cells (Das et al, 2013b).…”
Section: Resultsmentioning
confidence: 99%
“…This happens mostly in the initial phases of liver injury in rodent models, which have been used to study NASH progression. Patients with early phases of NASH occurrences also have reciprocated an M1 bias (Bertola et al, 2010). However, NASH progression is also associated with a delayed shift into profibrotic mechanisms, which might require an M2 polarization.…”
Section: Introductionmentioning
confidence: 99%
“…obesity-related gene expression changes in NAFLD in addition to inflammatory and immune system components of the liver (Baranova et al, 2005;Younossi et al, 2005b;Bertola et al, 2010). However, there is a lack of studies on expression changes of genes related to the absorption, distribution, metabolism, and elimination (ADME) processes in progressive human NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…Since we and others have found that CCL2 is also elevated in patients with alcoholic hepatitis and NASH (Fig. 1C) (7)(8)(9), although significantly lower than in HCV infection, it is possible that parallel gene-regulatory mechanisms may operate in non-HCV-mediated liver diseases.…”
Section: Discussionmentioning
confidence: 78%
“…CCL2, or monocyte chemotactic protein 1, is a cytokine (11 kDa) of the CC chemokine family secreted by a variety of cell types, including fibroblasts; peripheral blood mononuclear cells; monocytes; macrophages; and epithelial, endothelial, smooth muscle, and dendritic and microglial cells (3)(4)(5)(6). CCL2 is upregulated in patients with chronic liver diseases, such as alcoholic hepatitis, nonalcoholic steatohepatitis (NASH), and HCV infection, which are accompanied by inflammation (7)(8)(9). In mice, removal of the cytokine interleukin-6 (IL-6) and components of the IL-6 receptor (IL-6R) complex and STAT3 impairs CCL2 expression (10).…”
mentioning
confidence: 99%